Differential Suppression of Nicotiana benthamiana Innate Immune Responses by Transiently Expressed Pseudomonas syringae Type III Effectors - Gimenez-Ibanez, Selena; Hann, Dagmar R.; Chang, Jeff H.; Segonzac, Cécile; Boller, Thomas; Rathjen, John P. (Frontiers in Plant Science, 2018)
The plant pathogen Pseudomonas syringae injects about 30 different virulence proteins, so-called effectors, via a type III secretion system into plant cells to promote disease. Although some of these effectors are known to suppress either pattern-triggered immunity (PTI) or effector-triggered immunity (ETI), the mode of action of most of them remains unknown. Here, we used transient expression in Nicotiana benthamiana, to test the abilities of type III effectors of Pseudomonas syringae pv. tomato (Pto) DC3000 and Pseudomonas syringae pv. tabaci (Pta) 11528 to interfere with plant immunity. We monitored the sequential and rapid bursts of cytoplasmic Ca2+ and reactive oxygen species (ROS), the subsequent induction of defense gene expression, and promotion of cell death. We found that several effector proteins caused cell death, but independently of the known plant immune regulator NbSGT1, a gene essential for ETI. Furthermore, many effectors delayed or blocked the cell death-promoting activity of other effectors, thereby potentially contributing to pathogenesis. Secondly, a large number of effectors were able to suppress PAMP-induced defense responses. In the majority of cases, this resulted in suppression of all studied PAMP responses, suggesting that these effectors target common elements of PTI. However, effectors also targeted different steps within defense pathways and could be divided into three major groups based on their suppressive activities. Finally, the abilities of effectors of both Pto DC3000 and Pta 11528 to suppress plant immunity was conserved in most but not all cases. Overall, our data present a comprehensive picture of the mode of action of these effectors and indicate that most of them suppress plant defenses in various ways.